Vascular Closure Devices versus Manual Compression in Cardiac Interventional Procedures: Systematic Review and Meta-Analysis - Naidong Pang; Jia Gao; Binghang Zhang; Min Guo; Nan Zhang; Meng Sun; Rui Wang (Cardiovascular Therapeutics)
Backgrounds. Manual compression (MC) and vascular closure device (VCD) are two methods of vascular access site hemostasis after cardiac interventional procedures. However, there is still controversial over the use of them and a lack of comprehensive and systematic meta-analysis on this issue. Methods. Original articles comparing VCD and MC in cardiac interventional procedures were searched in PubMed, EMbase, Cochrane Library, and Web of Science through April 2022. Efficacy, safety, patient satisfaction, and other parameters were assessed between two groups. Heterogeneity among studies was evaluated by I2 index and the Cochran Q test, respectively. Publication bias was assessed using the funnel plot and Egger’s test. Results. A total of 32 studies were included after screening with inclusion and exclusion criteria (33481 patients). This meta-analysis found that VCD resulted in shorter time to hemostasis, ambulation, and discharge (p<0.00001). In terms of vascular complication risks, VCD group might be associated with a lower risk of major complications (p=0.0001), but the analysis limited to randomized controlled trials did not support this result (p=0.68). There was no significant difference in total complication rates (p=0.08) and bleeding-related complication rates (p=0.05) between the two groups. Patient satisfaction was higher in VCD group (p=0.002). Meta-regression analysis revealed no specific covariate as an influencing factor for above results (p>0.05). Conclusions. Compared with MC, the use of VCDs significantly shortens the time of hemostasis and allows earlier ambulation and discharge, meanwhile without increase in vascular complications. In addition, use of VCDs achieves higher patient satisfaction and leads cost savings for patients and institutions.